2014
DOI: 10.1016/j.yrtph.2014.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Locust bean gum safety in neonates and young infants: An integrated review of the toxicological database and clinical evidence

Abstract: Locust bean gum (LBG) is a galactomannan polysaccharide used as thickener in infant formulas with the therapeutic aim to treat uncomplicated gastroesophageal reflux (GER). Since its use in young infants below 12weeks of age is not explicitly covered by the current scientific concept of the derivation of health based guidance values, the present integrated safety review aimed to compile all the relevant preclinical toxicological studies and to combine them with substantial evidence gathered from the clinical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Cereals increase the infants’ caloric intake, possibly inducing excessive weight gain and altering the fat and protein energy ratio. Locust bean gum does not increase the caloric density, but may cause bloating . Home thickening of a regular formula increases the osmolarity, which may in itself induce reflux by increasing the number of transient lower oesophageal sphincter relaxations .…”
Section: Regurgitationmentioning
confidence: 99%
“…Cereals increase the infants’ caloric intake, possibly inducing excessive weight gain and altering the fat and protein energy ratio. Locust bean gum does not increase the caloric density, but may cause bloating . Home thickening of a regular formula increases the osmolarity, which may in itself induce reflux by increasing the number of transient lower oesophageal sphincter relaxations .…”
Section: Regurgitationmentioning
confidence: 99%
“…LBG is not susceptible to degradation by salivary amylase in contrast to starch thickeners [3]. However, the gastrointestinal adverse effects of formulas thickened with LBG have been debated because they increase defecation frequency and stool softening [6][7][8]. Therefore, this observational study aimed to evaluate the efficacy and tolerance of an LBG-thickened infant formula in infants presenting with moderate to severe regurgitation.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…These levels provide acceptable thickening properties for bottle feeding and clinical efficacy through dietary management. 123 The SCF in the EU previously concluded that the use of LBG in FSMP for infants for the dietary management of GER up to 10 g/L was acceptable. 123 Jurisdictions such as Europe, China, and the Russia-Kazakhstan-Belarus Customs Union currently approve the use of LBG in FSMPs at typical use levels of 5 g/L and upper end use levels of up to 10 g/L.…”
Section: Locust (Carob) Bean Gummentioning
confidence: 99%
“…123 The SCF in the EU previously concluded that the use of LBG in FSMP for infants for the dietary management of GER up to 10 g/L was acceptable. 123 Jurisdictions such as Europe, China, and the Russia-Kazakhstan-Belarus Customs Union currently approve the use of LBG in FSMPs at typical use levels of 5 g/L and upper end use levels of up to 10 g/L. Infant formulas containing LBG have been on the market in Europe and safely administered to many infants for more than 15 years.…”
Section: Locust (Carob) Bean Gummentioning
confidence: 99%